Shiga Toxin Subtypes of Non-O157 Escherichia coli Serogroups Isolated from Cattle Feces - Shridhar, Pragathi B.; Siepker, Chris; Noll, Lance W.; Shi, Xiaorong; Nagaraja, T. G.; Bai, Jianfa (Frontiers in Cellular and Infection Microbiology, 2017)
Shiga toxin producing Escherichia coli (STEC) are important foodborne pathogens responsible for human illnesses. Cattle are a major reservoir that harbor the organism in the hindgut and shed in the feces. Shiga toxins (Stx) are the primary virulence factors associated with STEC illnesses. The two antigenically distinct Stx types, Stx1 and Stx2, encoded by stx1 and stx2 genes, share approximately 56% amino acid sequence identity. Genetic variants exist within Stx1 and Stx2 based on differences in amino acid composition and in cytotoxicity. The objective of our study was to identify the stx subtypes in strains of STEC serogroups, other than O157, isolated from cattle feces. Shiga toxin gene carrying E. coli strains (n=192), spanning 27 serogroups originating from cattle (n=170) and human (n=22) sources, were utilized in the study. Shiga toxin genes were amplified by PCR, sequenced, and nucleotide sequences were translated into amino acid sequences using CLC main workbench software. Shiga toxin subtypes were identified based on the amino acid motifs that define each subtype. Shiga toxin genotypes were also identified at the nucleotide level by in silico restriction fragment length polymorphism (RFLP). Of the total 192 STEC strains, 93 (48.4%) were positive for stx1 only, 43 (22.4%) for stx2 only, and 56 (29.2%) for both stx1 and stx2. Among the 149 strains positive for stx1, 132 (88.6%) were stx1a and 17 (11.4%) were stx1c. Shiga toxin 1a was the most common subtype of stx1 among cattle (87.9%; 123/140) and human strains (100%; 9/9) of non-O157 serogroups. Of the total 99 strains positive for stx2, 79 were stx2a (79.8%), 11 (11.1%) were stx2c, 12 (12.1%) were stx2d. Of the 170 strains originating from cattle feces, 58 (34.1%) were stx2a subtype, 11 (6.5%) were stx2c subtype, and 11 were of subtype stx2d (6.5%). All but one of the human strains were positive for stx2a. Three strains of cattle origin were positive for both stx2a and stx2d. In conclusion, a number of non-O157 STEC serogroups harbored by cattle possess a wide variety of Shiga toxin subtypes, with stx1a and stx2a being the most predominant stx subtypes occurring individually or in combination.